Kinetics of circulating fetuin-A may predict mortality independently from adiponectin, high molecular weight adiponectin and prognostic factors in critically ill patients with sepsis: A prospective study. - Karampela, Irene; Kandri, Evangelia; Antonakos, Georgios; Vogiatzakis, Evangelos; Christodoulatos, Gerasimos Socrates; Nikolaidou, Athina; Dimopoulos, George; Armaganidis, Apostolos; Dalamaga, Maria (J Crit Care, 2017)
PURPOSE: Fetuin-A and adiponectin, major hepatokine and adipokine respectively, have been implicated in systematic inflammation. Our aim was to jointly investigate whether kinetics of circulating fetuin-A, adiponectin and its isoform HMWA predict 28-day mortality in sepsis. MATERIALS AND METHODS: In a prospective study, serum fetuin-A, adiponectin and HMWA were determined in 102 ICU patients fulfilling the diagnostic criteria of SEPSIS-3, at enrollment and one week after, and in 102 healthy controls matched on age and gender. RESULTS: Serum fetuin-A was significantly lower in septic patients than controls (p<0.001). Among septic patients, those with septic shock and nonsurvivors presented lower fetuin-A, but higher adiponectin and HMWA compared to patients with sepsis and survivors respectively, both at baseline and day 7 (p<0.001). Fetuin-A exhibited negative correlations with APACHE II, CRP, procalcitonin, adiponectin and IL-6 but a positive one with albumin. Reduced fetuin-A as well as lower serum kinetics of fetuin-A (HR: 0.55, 95% C.I. 0.34-0.91, p=0.02), adiponectin but not HMWA were independently associated with 28-day mortality adjusting for age, gender, BMI, APACHE II, septic shock and laboratory biomarkers. CONCLUSIONS: Circulating fetuin-A kinetics may be a prognostic biomarker in septic patients. More research is essential to elucidate fetuin-A's ontological role in sepsis pathophysiology.